Perancangan Audit Checklist dan Preaudit pada departemen Produksi di PT. Prima Dinamika Sentosa - Kevin Nikolay; Jani Rahardjo (Jurnal Titra, 2021)
PT. Prima Dinamika Sentosa is a manufacturing service company in the manufacture of footwear. The Children Place is an overseas customer who use the company’s. The Children Place gives requirement to conduct an internal audit for credibility of the company. The company conduct the internal audit once every 6 months. Usually the company’s internal audit is scheduled, so they could do some preparations to get a high audit score. But their preparations just an announcement. On this occasion the company asked the writer to help their internal audit preparations or the preaudit in the production process. The purpose of this preparation or the preaudit is to find out the suitability level in production process. The company also asked the writer to make an audit checklist question which one also used for their internal audit question. The writer will use the audit checklist question as written in ISO 19011:2018 to find out the suitability level in the production process when conduct the preaudit. The non-conformities that have been found will be searched for the cause with the fishbone diagram, and then the writer will provide suggestions for improvement, so when the company conduct the internal audit, the score will be better.